Chloramine Salt Mediated Oxidative Halogenation of Terminal Alkynes with KI or NaBr: Practical Synthesis of 1-Bromoalkynes and 1-Iodoalkynes - Liu, Xiaozu; Chen, Guojun; Li, Chenglong; Liu, Peijun (Synlett, 2018)
A direct oxidative halogenation of terminal alkynes has been realized using chloramine-B as the oxidant and KI or NaBr as the halogen source. This reaction enables a general and practical access to synthetically valuable 1-bromoalkynes and 1-iodoalkynes in good to excellent yields under mild reaction conditions.
Keywords: oxidative halogenation; 1-bromoalkynes; 1-iodoalkynes; chloramine salt; terminal alkynes